Accounting for seedling performance from nursery to outplanting when reforesting degraded tropical peatlands - Harrison, Mark E. (2024)
Reforestation is promoted to address the dual global climate and biodiversity crises. This is particularly relevant for carbon-rich, biodiverse tropical peatlands, for which active reforestation typically involves two post-germination stages: nursery rearing of seedlings, then outplanting. Yet, linkages between these stages and cumulative seedling performance are rarely quantified during tropical peatland reforestation. By monitoring tree seedling survival and growth, we investigate factors influencing seedling performance (species identity, seedling source, treatments, and climate), whether nursery performance predicts outplanting performance, and calculate cumulative survival (nursery plus outplanting) in Sebangau National Park, Indonesian Borneo. Standardized survival at 2 years was higher in the nursery (mean 67% across 40 species) than outplanting (44% across 24 species). For nursery and outplanting, species identity was the main source of variation in survival and height growth. Seedling source, treatments, site condition, and precipitation had no significant impact on survival but did influence growth in some cases. Nursery survival did not predict outplanting survival, but nursery height did predict outplanting height. Across species, around a quarter of seedlings survived from nursery to outplanting over 4 years. Cumulative survival represents a more realistic basis for assessing the genetic and other resource costs of tropical peatland reforestation. Our two-phase approach identified outplanting as the greater bottleneck to cumulative seedling survivability. We argue that the nursery stage may be used to harden seedlings for degraded peatland conditions by selecting more relevant treatments (e.g. flooding) and screening for resilience to common disturbances (e.g. fire) to enhance outplanted, and thus cumulative, seedling survival.